Improving Performances of Interior Permanent Magnet Synchronous Motors by Using Different Rotor Angles - Hung Bui Duc; Dinh Bui Minh; Bao Doan Thanh; Tu Pham Minh (My University, 2023)
Improving Performances of Interior Permanent Magnet Synchronous Motors by Using Different Rotor Angles
Keywords: Hiệu suất IPMSM; Góc rô-to; Động cơ đồng bộ